Compressibility of the composite material with fiber filler and nanodimensional polyurethane matrix for road and hydro engineering construction - Victor G. Nazarov; Alexander V. Dedov; Elena S. Bokova (Нанотехнологии в строительстве, 2023)
ABSTRACT: Introduction. The aim of the research is to study the compressibility of composite materials obtained by varying the degree of impregnation of a non-woven needle-punched cloth with an aqueous dispersion of polyurethane. Materials and research methods. Non-woven needle-punched cloth made of polyethylene terephthalate fibers (TU 6-13-0204077-95-91) with a linear density of 0.33 tex (diameter 20–25 microns) was used as objects of research. For impregnation, an aqueous dispersion of anionic stabilized aliphatic polyethiruretane of the brand IMPRANIL DL 1380 (PRC) with a dry residue of 40% was used. The compressibility of canvases and composite materials was established using the ICH indicator according to GOST 577-68 with an accuracy of measuring the thickness of ± 0.001 mm. Results and discussion. An approach is proposed to establish the relationship between the degree of compressibility of composite materials and the load and to obtain an equation for predicting the degree of compressibility of composite materials from the degree of impregnation and load. Optimal loading conditions of the composite material with a minimum degree of compressibility has been established. Conclusion. The optimal degree of impregnation of a non-woven needlepunched fabric made of polyethylene terephthalate fibers with a diameter of 20–25 microns with polyurethane dispersion is 0.5.